pengaruh Pengaruh Model Pembelajaran Direct Instruction Terhadap Hasil Belajar Teknik Dasar Guling belakang Senam Lantai Pada Siswa MTs - Dian Muchlis Aufa; Hilmy Aliriad; Benny Widya Priadana (Jurnal Porkes, 2026)
The problem in this study was the low learning outcomes of basic back roll techniques in floor gymnastics among students at MTs Al-Mahmudi Jatiroo, which was caused by limited understanding of movement, fear, and inappropriate learning strategies. The purpose of this study was to analyze the effect of applying the direct instruction learning model on learning outcomes in basic back roll techniques. The method used was a one-group pretest-posttest design with a sample of 20 ninth-grade students selected through total sampling. Data were collected through a performance test assessed using an aspect-based assessment rubric, then analyzed using a paired sample t-test with a significance level of 0.05. The results showed that the average pretest score of 54.80 increased to 81.30 on the posttest, with a difference of 26.50. The discussion revealed that the systematic learning structure in the direct instruction model through demonstration, guided practice, and direct feedback was effective in improving students' motor skills and confidence. The conclusion of this study is that the direct instruction model has a significant effect on improving learning outcomes in basic back roll techniques, so it can be recommended as an effective learning alternative in physical education subjects.